Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors